2010
DOI: 10.2466/pms.110.c.1059-1064
|View full text |Cite
|
Sign up to set email alerts
|

Background Music and Cognitive Performance

Abstract: The present experiment employed standardized test batteries to assess the effects of fast-tempo music on cognitive performance among 56 male and female university students. A linguistic processing task and a spatial processing task were selected from the Criterion Task Set developed to assess verbal and nonverbal performance. Ten excerpts from Mozart's music matched for tempo were selected. Background music increased the speed of spatial processing and the accuracy of linguistic processing. The findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
(23 reference statements)
1
19
0
Order By: Relevance
“…Moreover, analysis of tempo, lyrics, and genre in the present study revealed no significant effects on RT, variability of RT, or indeed on thought-probe response proportions. These null results represent a failure to replicate past studies on tempo (e.g., Amezcua et al, 2005;Angel et al, 2010), lyrics (e.g., Darrow et al, 2006;Drai-Zerbib and Baccino, 2017;Shih et al, 2012) and on genre (e.g., Chew, 2010;Corhan and Gounard, 1976;Davies et al, 1973). The absence of any significant effect of musical parameters (whether tempo, lyrics, or genre) may be a by-product of the use of selfselected music in the current study, making it bound to represent a less satisfactory test of their role than studies directly manipulating these musical parameters within the individual.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, analysis of tempo, lyrics, and genre in the present study revealed no significant effects on RT, variability of RT, or indeed on thought-probe response proportions. These null results represent a failure to replicate past studies on tempo (e.g., Amezcua et al, 2005;Angel et al, 2010), lyrics (e.g., Darrow et al, 2006;Drai-Zerbib and Baccino, 2017;Shih et al, 2012) and on genre (e.g., Chew, 2010;Corhan and Gounard, 1976;Davies et al, 1973). The absence of any significant effect of musical parameters (whether tempo, lyrics, or genre) may be a by-product of the use of selfselected music in the current study, making it bound to represent a less satisfactory test of their role than studies directly manipulating these musical parameters within the individual.…”
Section: Discussionmentioning
confidence: 69%
“…Because baseline arousal level varies across people and depends on factors, such as personality (e.g., Cassidy & MacDonald, 2007;Furnham & Allass, 1999;Salame & Baddeley, 1982), the 'arousingness' and the qualities of the music required to achieve optimal arousal and performance also varies across people. Nevertheless, we conducted exploratory analyses of the impact on sustained attention of qualities of the preferred music stimuli, namely tempo, lyrics and genre, as these have all been shown to impact attention and performance (see, e.g., Amezcua, Guevara, & Ramos-Loyo, 2005;Angel, Polzella, & Elvers, 2010;Chew, 2010;Corhan & Gounard, 1976;Darrow et al, 2006;Davies et al, 1973;Drai-Zerbib & Baccino, 2017;Shih et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be speculated that this phenomenon refers to a more general boosting property of music, which has been supported by empirical investigations on the effect of listening to background music on performance during various cognitive tasks. For example, evidence of improvements in verbal memory encoding [ 13 ], autobiographical memory in Alzheimer patients [ 14 ], declarative memory [ 15 ], verbal and visual processing speed [ 16 ], arithmetic skills [ 17 ], reading [ 18 ], and learning second languages [ 19 ] has been accumulated. According to other authors [ 20 ], there would be no compelling evidence of a special link between listening to Mozart (or to any Classical music) and visuospatial (or spatial-temporal) abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Music has been used to treat soldiers in pain and traumatic injuries during World War I and II [2]. It has also been found to reduce sleeping problems [3], to improve speed of spatial processing and the accuracy of linguistic processing [4], has been used as an ergogenic aid during various physical activities and sports [5] and has also been reported to hasten post exercise recovery [6], decrease rate of perceived exertion (RPE) and also lower cardiovascular response to exercise [7]. There is a long history of beneficial effects of using music in Manuscript received 10 th August 2016 Reviewed: 24 th August 2016 Author Corrected: 5 th September 2016 Accepted for Publication 20 th September 2016 sports and exercise.…”
Section: Introductionmentioning
confidence: 99%